The Effects of Low Self-Control and Desire-for-Control on White-Collar Offending: A Replication. Issue 11 (1st November 2016) - Craig, Jessica M.; Piquero, Nicole Leeper
ABSTRACT: To further our understanding of the similarities and differences between street-level and white-collar offending, two personality traits were used to predict offending intentions. The independent and joint roles of low self-control and desire-for-control on intentions to engage in embezzlement, credit card fraud, and shoplifting were assessed. Findings suggested that while low self-control was predictive of intentions to offend, the impact of desire-for-control varied based on the respondent's level of self-control. In contrast to prior studies, desire-for-control reduced offending intentions, but only among those with high self-control. A discussion of these findings is offered, along with study limitations and future directions.